HUBUNGAN KONSUMSI PROTEIN, STATUS GIZI DENGAN KEJADIAN GOUT ARTHRITIS PADA PENGUNJUNG DI PUSKESMAS HARAPAN RAYA - Besti Verawati; Nopri Yanto; Sukanti Rahayu (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2020)
Background: Gout arthritis is the disease because of purine abnormal metabolism marked by the increase of uric acid level in blood. Gout arthritis can also cause disorder in kidney. This research aims to analyze the correlation between protein consumption, nutrient status, and gout arthritis occurance on the visitors of Community Health Center Harapan Raya in 2019. Method: This research used cross sectional study design and was conducted on 11-29th of July 2019 with population all visitors at Community Health Center Harapan Raya Pekanbaru City and total samples were 87 people obtained by using Accidental Sampling. The techniques of data collection were by using questionnaire and food recall 2 x 24 hours method, body weight measurement and body height measurement and uric acid level check. Data analysis was by using univariate and bivariate with Chi Square test. The Result: Respondents’ protein consumption is categorized into low and their nutrient status is excessive. There is correlation between protein consumption (p=0.024) and nutrient status value (p=0.000). Conclusion: There is correlation between protein consumption, nutrient status and gout arthritis occurance on the visitors at Community Health Center Harapan Raya in 2019.